Pengaruh Brand Storytelling Marketing dan Emotional Connection Terhadap Keputusan Pembelian Teh Botol Sosro (Studi pada Konsumen di Kota Malang) - Aisyah, Rahmatika Nur; Basalamah, Muhammad Ridwan; Dianawati, Eris (UNIVERSITAS ISLAM MALANG, 2025)
Abstract Increasingly fierce industry competition encourages companies to implement more effective marketing strategies, one of which is through brand storytelling marketing that builds emotional connections with consumers. This study analyzes the effect of brand storytelling marketing and emotional connection on purchasing decisions for Teh Botol Sosro in Malang City. The research method used is quantitative with survey techniques on 75 respondents. The analysis technique used is multiple linear regression analysis which shows that both brand storytelling marketing and emotional connection have a effect on purchasing decisions. Consumers are more interested and loyal to brands that are able to build strong stories and emotional attachments. This research emphasizes the importance of companies in developing compelling brand communication and building emotional connections with consumers to increase market competitiveness. Keywords: Brand Storytelling Marketing, Emotional Connection, Purchase Decision.